Effects of a reflective cultural audit intervention on multicultural and social justice counselling competencies of counselling students. Issue 4 (24th June 2022) - Kim, Nayoung; Oh, Seungbin; Han, Eunae
Abstract: Enhancing multicultural and social justice counselling competencies (MSJCC) has been important in the counselling field for a number of years. As such, counsellor educators are called to provide the relevant education for counselling students. To identify ways to increase counselling students' MSJCC, the researchers conducted an experimental study investigating the effects of reflective practice on MSJCC of counselling students. Participants were recruited from a large university in the U.S. and completed a survey at the beginning and the end of their practicum semester. They were divided into an experimental ( n  = 35) and control ( n  = 37) group. Students in the experimental group wrote reflective journals after working with clients from different backgrounds. Specifically, we used the intervention derived from cultural auditing where individuals answer questions based on the prompts that facilitated participants' reflection regarding their counselling sessions. In our study, we selectively provided participants with the prompts from the cultural auditing process. For instance, we asked what their initial reactions were to a specific client, what those reaction may indicate about their own beliefs, values and assumptions, what the client's rationale was for the problem and how it may fit with the ways that problems were conceptualised within their culture. Based on these prompts, counselling students in the experimental group wrote reflective journals. An analysis of covariance (ANCOVA) was employed. Results showed that MSJCC was higher for those in the control group than those in the experimental group, F (286.573, 1) = 5.119, p  = .027, η p 2  = 0.071. Implications for future research are discussed.